2012
DOI: 10.1177/0091270011421912
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics, Pharmacokinetics, and Safety of AM211: A Novel and Potent Antagonist of the Prostaglandin D2 Receptor Type 2

Abstract: The prostaglandin D(2) receptor type 2 (DP2) and its ligand, PGD(2), have been implicated in the development of asthma and other inflammatory diseases. The authors evaluated the pharmacodynamics, pharmacokinetics and safety of [2'-(3-benzyl-1-ethyl-ureidomethyl)-6-methoxy-4'-trifluoromethyl-biphenyl-3-yl]-acetic acid sodium salt (AM211), a novel and potent DP2 antagonist, in healthy participants. Single and multiple doses of AM211 demonstrated dose-dependent inhibition of eosinophil shape change in blood with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Multiple CRTh2 receptor antagonists are under clinical investigation, and there has also been a significant degree of turnover of CRTh2 antagonists in clinical development (AZD1981, setipiprant, AZD5985, RG7185), the main reasons disclosed being low clinical efficacy (setipiprant) or undesirable PK profiles . For example, MK7246 was discontinued because of high intersubject variability, and studies on AM211 also reported high intersubject variability and enterohepatic recirculation . In contrast, fevipiprant has demonstrated efficacy in phase 2 studies in patients with asthma and is now proceeding toward development phase 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple CRTh2 receptor antagonists are under clinical investigation, and there has also been a significant degree of turnover of CRTh2 antagonists in clinical development (AZD1981, setipiprant, AZD5985, RG7185), the main reasons disclosed being low clinical efficacy (setipiprant) or undesirable PK profiles . For example, MK7246 was discontinued because of high intersubject variability, and studies on AM211 also reported high intersubject variability and enterohepatic recirculation . In contrast, fevipiprant has demonstrated efficacy in phase 2 studies in patients with asthma and is now proceeding toward development phase 3.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, fevipiprant has demonstrated efficacy in phase 2 studies in patients with asthma and is now proceeding toward development phase 3. Clinical efficacy was observed as well as strong mechanistic effects, including a reduction in lung eosinophils that was demonstrated in a recently published mechanistic study …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we identified RARE elements in this promoter region, and found that differential allelic occupancy at different positions determines modifications in transcription factor binding that could explain differential promoter activation. All these results provide new insights into the effects of RA and treatments based on PTGDR modulators [36], although more studies are needed to assess the relevance of these results to allergic diseases.…”
Section: Transcription Factor Binding Site Analysis In the 5'-flankinmentioning
confidence: 89%
“…The two CRTH2 antagonists in phase I clinical trials are AM211 [(2′-[3-benzyl-1-ethyl-ureidomethyl]-6-methoxy-4′-trifluoromethyl-biphenyl-3-yl)-acetic acid sodium salt] [86] and RG7185. To the date of reporting, three CRTH2 antagonists have been tested in phase II trials, i.e.…”
Section: Drugs Targeting Crth2 and Crth2/dprmentioning
confidence: 99%